Development of a Barcode-Based Student Worksheet (LKPD) for the Physical Education, Sports, and Health (PJOK) to Enhance Learning Outcomes of Third-Grade Elementary School - Yudesta, Yudesta Erfayliana (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
This study aims to develop and evaluate a barcode-based Student Worksheet (LKPD) designed to improve learning outcomes in Physical Education, Sports, and Health (PJOK) for third-grade elementary school. The problem emerged from observations and interviews conducted at SDN 1 and SDN 2 Merbau Mataram, which revealed that the learning process was still dominated by lecture-based instruction and standard textbooks let to student boredom, difficulty maintaining focus, and limited exposure to technology-supported teaching materials. The study adopted a Research and Development (R&D) approach employing the ADDIE model, encompassing five phases: Analysis, Design, Development, Implementation, and Evaluation. Validation results demonstrated that the barcode-based LKPD was very valid, achieving score of 93.3% from content experts, 95.4% from media experts, and 89.1% from language experts. The effectiveness test demonstrated a moderately effective category, supported by the results of the normality test (0.010 for the small-scale trial; 0.021 for the large-scale trial), a homogeneity test result of 0.199, a t-test significance value of 0.0219, and an N-Gain score of 0.611. Therefore, the barcode-based LKPD developed serve as an innovative alternative learning medium that effectively supports PJOK instructional activities and significantly enhances third-grade elementary school students’ learning outcomes